Dung beetles in the Central Catchment Nature Reserve, Singapore - Cheong, Samuel Kit Siang (Nanyang Technological University, 2024)
Dung beetles play many vital roles in the ecosystem, from nutrient cycling to parasite control. Presently, the diversity and distribution of dung beetles in Singapore’s largest forest path, the Central Catchment Nature Reserve (CCNR), has not been extensively documented. Additionally, dung beetles found on the ground and in the canopy have varying biodiversity due to niche partitioning.